The Correlation Between Potential “Anti- Cancer” Trace Elements and the Risk of Breast Cancer: A Case-Control Study in a Chinese Population - Xue, Heng; Qiao, Rui; Yan, Lailai; Yang, Siyu; Liang, Yongming; Liu, Yaqiong; Xie, Qing; Cui, Ligang; Cao, Bing (Frontiers in Oncology, 2021)
Backgrounds: Breast cancer is a heterogeneous disease without clear pathogenesis and effective primary prevention. The “anti-cancer” effects of several trace elements have received increasing attention in recent years. The main purpose of current study is to explore the difference of three potential “anti-cancer” trace elements Selenium (Se), Molybdenum (Mo), Strontium (Sr) between patients with malignant breast tumors and healthy controls. Methods: We conducted a case-control study in 45 patients with malignant breast tumors as cases and 95 healthy volunteers as controls from Peking University Third Hospital, Beijing, China. The serum concentrations of trace elements were evaluated by using inductively coupled plasma mass spectrometry (ICP-MS). Results: The cases may have a lower Se levels when compared with controls (cases: 106.22ng/ml, SD: 20.95 ng/ml; controls: 117.02 ng/ml, IQR: 22.79 ng/ml, p =0.014). High levels of Se were a protective factor from breast cancer after adjusting the potential confounders of age, BMI, smoking, drinking and menopause status (OR = 0.395, 95% CI, 0.178,0.877, p = 0.023). The levels of Sr were lower in cases with high histologic grade when compared to low histologic grade (low histologic grade: 49.83 ng/ml, IQR: 41.35-62.60 ng/ml; high histologic grade: 40.19 ng/ml, IQR: 39.24-47.16 ng/ml, p<0.05). Conclusions: Our findings herein supported that Se has protective effects to avoid malignant breast tumors and Sr has protective effects to avoid poorly differentiated of malignant breast tumors. Exploring “anti-cancer” related trace elements and their associations with breast cancer will assist for the early prevention and intervention for the disease.